2016
DOI: 10.4314/star.v4i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and Chemical Control of White Mango Scale (<i>Aulacaspis tubercularis</i>) in Central Rift Valley

Abstract: Occurrence of White Mango Scale (WMS), Diaspididae), in Ethiopia was known in 2010. It had remained confined to western Ethiopia where local mango trees of old age found until recently. Leaf samples infested by the pest were brought to Melkassa Agricultural Research Center (MARC) for diagnosis in June 2014. Hence, a survey to determine occurrence and distribution of the pest on mango orchards in the Central Rift Valley was conducted in August 2014. Four out of seventeen fields surveyed were infested by the pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
1
17
0
1
Order By: Relevance
“…Khat chewers were 5.426 times (AOR: 5.426; 95% CI: 1.811–16.256; and p =0.003) at risk of hypertension than non-khat chewers. This finding was similar with the findings of the studies done in Addis Ababa (AOR: 5.0; 95% CI: 1.91–13.06; and p =0.001) [ 61 ] and in Jimma town, southwest Ethiopia (AOR: 1.50; 95% CI: 1.45–2.87; and p < 0.001) [ 62 ]. The leaves of the khat plant contain amphetamine-like compounds (cathinone and cathine) which increase vasoconstriction and heart rate which in turn increase blood pressure [ 63 ].…”
Section: Discussionsupporting
confidence: 90%
“…Khat chewers were 5.426 times (AOR: 5.426; 95% CI: 1.811–16.256; and p =0.003) at risk of hypertension than non-khat chewers. This finding was similar with the findings of the studies done in Addis Ababa (AOR: 5.0; 95% CI: 1.91–13.06; and p =0.001) [ 61 ] and in Jimma town, southwest Ethiopia (AOR: 1.50; 95% CI: 1.45–2.87; and p < 0.001) [ 62 ]. The leaves of the khat plant contain amphetamine-like compounds (cathinone and cathine) which increase vasoconstriction and heart rate which in turn increase blood pressure [ 63 ].…”
Section: Discussionsupporting
confidence: 90%
“…The reported efficacy vary from one research to the other depending on the stage of pest when application was made, the efficiency of the application process and the type of trial (laboratory versus field trial). Bi-weekly application of Movento and Methidathion 400EC pesticides was found to cause up to 90% and 74% mortality of white mango scale insects after the fifth round of applications respectively (Ayalew et al, 2015). Here, Movento product was recommended for use in the control of the pest.…”
Section: Integrated Pest Management Strategies For a Tubercularis Control In Sub-saharan Africa Regionmentioning
confidence: 99%
“…Being an invasive pest, the information about the pest and its management practices is less available for researchers, policymakers, and farmers in the SSA region. In fact, most research work in the region has focused around assessing the distribution and population dynamics (Babege et al, 2017;Djirata et al, 2019;Teshale et al, 2019) with a few trying to answer questions around management practices (Abo-Shanab, 2012;Ayalew et al, 2015). The coverage of these type of research is narrow in the region, mainly in Ethiopia, Egypt, Kenya and South Africa.…”
mentioning
confidence: 99%
“…Chemical control option is most used when crop are heavily infested with the pest [35]. Among evaluated insecticides, granular systemic insecticide Spark 250 WG, Spirotetramat has been reported with promising results for white mango scale control [36,37] reported that higher population reduction was by Folimat and followed with Closer 240. However, some non-target insects were dead on trees treated with Folimat.…”
Section: Chemical Control Methodsmentioning
confidence: 99%